MOTIVASI KETERLIBATAN PENGURUS LINGKUNGAN DALAM KEGIATAN GEREJANI - Melania, Agnes; Wilhelmus, Ola Rongan (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2023)
Motivation is the basic thing that moves everyone in achieving the desired goals. In church life, motivation plays an important role, especially for every leader in Church circles, because clear motivation helps every leader to move their members, namely the people, to be more active and involved in church life. The research methodology, which was conducted qualitatively, is expected to reveal how motivation is very important in supporting environmental administrators in ecclesiastical activities.